(untitled) (International Seven Journal of Health Research, 2023)
Introduction: The elderly have a perception of aging related to the choices made throughout life, also considering financial resources, family support, social network, and elderly groups. Objective: To analyze the perception of aging of participants in social work with elderly people from the Social Service of Commerce (Sesc) in Ceará. Method: This is a descriptive study with a qualitative approach. For data collection, the conversation wheel technique was used, with the participation of 126 elderly people - 110 women (87%) and 16 men (13%) -, aged between 60 and 102 years (73.69 ± 7.12 ). The narratives were analyzed using the Content Analysis Method and the categories of aging, activities, and coexistence were identified. Results: It was observed that aging is the result of the history of these elderly people and a natural stage of life, while the activities are a starting point for the feeling of renewal of life as opposed to accommodation, and coexistence was the positive element to establish a relationship intimate with an exchange of voluntary affections of friendships through the interaction provided by the open space and the exchange of knowledge. Final considerations: The study presented narratives that encourage empowerment and the ability of the elderly to see themselves as active in society. DOI:https://doi.org/10.56238/isevjhv2n2-011